Enti ecclesiastici e riforma del Terzo settore. Profili canonistici (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Riforma del Terzo settore e servizio della carità nella Chiesa - 2. La riforma del Terzo settore e le nuove sfide per gli enti ecclesiastici - 3. Il Motu proprio “Intima Ecclesiae natura” e l’evoluzione dell’ordinamento canonico - 4. Il Codice del Terzo settore e la sua applicazione agli enti ecclesiastici - 5. Implicazioni per gli enti della Chiesa: l’esigenza di trasparenza - 6. Il principio della trasparenza nella dottrina canonistica - 7. Il “patrimonio destinato”: implicazioni nell’ordinamento canonico - 8. Attività diverse e controlli canonici: la sfida della governance e della gestione in un contesto concordatario - 9. Osservazioni conclusive.Catholic Church entities and the reform of the Third sector in Italian legislation. Canonical implicationsABSTRACT: This paper deals with the canonical implications of Italy’s recent Third sector reform in Italian legislation (d. lgs n. 117/2017) for Catholic Church entities and/or agencies for charitable purposes. It starts with some preliminary remarks on the recent evolution of Canon Law concerning the discipline of charitable organizations and agencies that followed the Motu proprio Intima Ecclesiae natura, issued by Pope Benedict XVI in December 2012. It then examines the general framework of the new regulation of non profit organizations in Italian law, emphasizing the pros and cons (opportunities and risks) of its application to religious entities, particularly those connected to the Catholic Church, which in Italy traditionally enjoy a special discipline safeguarding their canonical structure and purposes. The paper then focuses on the impact of the new civil regulation that allows a wide range of charitable initiatives on behalf of religious organizations, on the governance of Catholic Church entities, which are submitted to the directives and authorizations of ecclesiastical authorities. Finally, it draws some conclusive remarks on the need to update and reform some administrative rules and praxis concerning the administration and finance of charitable institutions in Canon Law.
Keywords: Enti religiosi